Assessment of Correlation between Carotid Artery Calcification and Alveolar Bone Loss: A Retrospective Study of CBCT Findings - Nilsun Bagis; Umut Seki; Kaan Orhan (Journal of Clinical and Diagnostic Research, 2019)
Introduction: One of the main causes of the cardiovascular diseases is atherosclerosis which is characterised by thickening and the loss of elasticity of the arterial walls. Chronic periodontitis is one of the risk factor of coronary artery disease. Immune response to chronic periodontitis may exert an endothelial cytotoxic effect known to be a risk for atherosclerosis and periodontal pathogens have been demonstrated in atherosclerotic plaques removed during carotid endarterectomy in previous studies. Aim: The aim of this study was two folded: (1) to figure out the prevalence of Carotid Artery Calcification (CAC) using Cone Beam Computed Tomography (CBCT) images with a Field of View (FOV) including entire craniofacial area; and (2) to examine the correlation between CAC and radiographic evidence of alveolar bone loss. Materials and Methods: For this retrospective study, CBCT images of 256 patients were chosen. The images were retrospectively evaluated for having CAC and divided groups as with CAC and without CAC (control subject). The patients who had CAC were further evaluated regarding alveolar bone loss with CBCT images according to age and gender, without systemic disease. All images were independently observed by two observers. Alveolar bone loss investigations were performed on maxillary and mandibular teeth on panoramic radiographs according to Progressive Rate Index (PRI). Pearson chi-square statistical analyses were made among groups as alveolar bone loss according to CAC (Unilateral/ Bilateral) (p<0.05) and Student t-test were among groups (CAC and control) according to age and gender (p<0.05). Results: Of all, 60 patients (23.4%) had CAC (age range 35-70 year; 25 female-35 male; mean age 44.5 years). The rest 196 patients served as control subjects. While alveolar bone loss did increase considerably according to age groups, statistical difference was found between group younger than 50 and 60-70 age group (p<0.05). The patients with CAC had higher alveolar bone loss than the control subjects according to all age groups and gender (p<0.05). Conclusion: Radiographic parameters according to PRI revealed that alveolar bone loss was more prevalent among subjects with carotid artery calcifications. Periodontal status and its role as a risk factor in triggering cardiovascular events should be taken into account by not only dental professionals but also the medical professionals in order to plan prevention programs.